Destination Branding in The Digital Age: Social Media, Brand Equity, And Tourist Loyalty In Batam - Meliawati; Sihombing, Dame Afrina; Lily Purwianti (Media Wisata, 2025)
Batam is the largest contributor to the number of foreign tourists to the Riau Islands and has great potential as the main entry point for tourism. This research aims to determine tourist characteristics and the influence of social media communication and brand equity on destination brand loyalty and tourist satisfaction in Batam. This research applies quantitative methods using the population of foreign tourists who come to Batam. Apart from that, the sample used is data on foreign tourists who come to Batam for the purpose of traveling. This research obtained the results that social media communication and brand equity factors influence tourist satisfaction, then tourist satisfaction has a positive influence in mediating these factors on destination brand loyalty. The limitation of this research is the scope of the research which only involves foreign  tourists who travel to Batam.